IMPLEMENTATION OF EMPLOYEE ABSENCE INFORMATION SYSTEM USING QR CODE AT INDOMEDIA GROUP - Ramadan Duwi Susanto; Nining Suharyanti (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2025)
The advancement of information technology has driven digital transformation across various sectors, including employee attendance management in companies. Indo Media, a company engaged in daily news broadcasting, requires an attendance recording system that is fast, accurate, and accessible in real time. This study aims to design and develop a web-based employee attendance information system capable of handling clock-in and clock-out processes by utilizing QR Code technology as the attendance identification medium. The system development method used is Rapid Application Development (RAD), which emphasizes speed and iteration in the system-building process, starting from requirements planning, system design using UML (Use Case Diagram, Class Diagram, and Activity Diagram), to prototype implementation and user evaluation. The system is also equipped with a relational database structure and a Logical Record Structure (LRS) designed to support efficient attendance data management. The result of this study is a web-based application that allows employees to perform attendance independently and enables administrators to monitor and manage attendance data comprehensively. This system improves time efficiency, reduces the risk of data entry errors, and provides fast and accurate access to attendance records.